Factors influencing access, quality and utilisation of primary healthcare for patients living with hypertension in West Africa: a scoping review - Tolib Mirzoev; Pablo Perel; Irene Akua Agyepong; Evelyn K Ansah; Kezia Naa Amerley Akosua Amarteyfio; Eugene Paa Kofi Bondzie; Veronika Reichenberger; Nana Efua Enyimayew Afun; Albert Kofi Mensah Cofie; Mary Pomaa Agyekum; Paul Lamptey (BMJ Open)
Objectives Hypertension is one of the most prevalent non-communicable diseases in West Africa, which responds to effective primary care. This scoping review explored factors influencing primary care access, utilisation and quality for patients with hypertension in West Africa.Design Scoping review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for scoping reviews.Data sources Published literature from PubMed, Embase, Scopus, Cairn Info and Google Scholar, between 1 January 2000 and 31 December 2023.Eligibility criteria Systematic reviews, observational studies and reports involving participants aged 18 years and above, written in English, French or Portuguese, were included. Clinical case series/case reports, short communications, books, grey literature, randomised control trials, clinical trials, quasi-experiments, conference proceedings and papers on gestational hypertension and pre-eclampsia were excluded.Data extraction and synthesis Data from included studies were extracted onto an Excel spreadsheet and synthesised qualitatively using thematic analysis structured by the components of the overall review question.Results The search yielded a total of 5846 studies, 45 papers were selected for full review and 16 papers were eventually included. Macro (contextual) barriers included economic, funding and geographical barriers. Meso (health system) factors include access to medications, tools, equipment and other supplies, out-of-pocket payments, availability of health insurance, health workers numbers, capacity and distribution. Micro (community and patient factors) barriers included financial barriers and limited knowledge, whereas facilitators included the availability of alternative providers and community and household support. These factors are interconnected and complex and should be addressed as a whole to reduce the burden of hypertension in West Africa.Conclusion Multiple complex and interrelated factors at contextual, health systems, community and patient levels act as barriers and enablers to access, utilisation and quality of primary care for hypertension in West Africa. Improving primary care and outcomes will, therefore, require multilevel multifaceted interventions.